VARIASI SUMBER KARBON TERHADAP PRODUKSI BIOSURFAKTAN OLEH BAKTERI HALOFILIK ISOLAT TAMBAK GARAM KAJHU ACEH BESAR - Rahmad Rizki Fazli; Latifah Hanum; Mieke Alvionita; Said Ali Akbar (Lantanida Journal, 2022)
This research has isolated one type of halophilic bacterial strain from the salt pond of Kajhu Village with the code KJ-AB2. This bacterium grew optimally at 10% (w/v) NaCl so it was classified as moderate halophilic bacteria. Several types of halophilic bacteria are known to produce biosurfactants. Biosurfactants are surface active agents that are widely used in several pharmaceutical, food dan petroleum industries. The production of biosurfactants is strongly influenced by the type of carbon source used for bacterial growth. Olive oil, palm oil, sunflower oil, glucose dan glycerol are types of carbon sources used to see their effect in producing biosurfactants. This isolate growed well on the five carbon sources with an average OD600 2.001±0.293 at 72 hours of fermentation. Biosurfactant production was measured by oil spreading test (OST) every 24 hours until 120 hours of fermentation. The highest OST value was obtained when KJ-AB2 isolate was grown on biosurfactant production media using olive oil, sunflower oil dan palm oil with an average OST value of 5.6±0.6 cm, 4.7±0.6 cm, dan 4.6±0.7 cm, respectively.